Occurrence and risk factors associated with canine leptospirosis - Kikuti,M (2012)
Leptospirosis is a globally distributed emerging zoonosis. Dogs are commonly affected and although other serovars can cause canine leptospirosis, Leptospira interrogans serovar Canicola is primary found in these animals. A retrospective study was conducted using a database of 1195 dogs tested for Leptospira infection from 2003 to 2010 at the Laboratory of Zoonosis Diagnosis at the Veterinary Hospital of São Paulo State University (UNESP) in Botucatu, São Paulo state, Brazil. The seroprevalence of infected dogs was 20.08% (240/1195), and the most prevalent serovars were Canicola (6.7%), Copenhageni (5.0%), Icterohaemorrhagiae (2.9%), Autumnalis (2.9%), Pyrogenes (2.8%), Pomona (2.0%), Hardjo (2.0%), Australis (1.8%), Bratislava (1.6%), Cynopteri (1.4%), Grippotyphosa (1.3%) and Djasiman (1.0%). By univariate analysis, the variables age and breed were not statistically related to the infection, while gender and season were. The effects of gender were also noticeable related to serovars Australis, Canicola and Hardjo. In multivariate analysis, the level of significance (p-value) of season was suppressed by gender, indicating possible collinearity between those two variables.